Effect of Kappa Carrageenan on Physicochemical Quality and Sensory Attributes in Development of Chicken Meat Bites - Biswas, P.; Biswas, A.K.; Bera, I. (Journal of Meat Science, 2018)
Many studies were conducted on the use of carrageenan as fat replacer but lacks useful information for its functional activity in meat  products. Therefore, aim of this study was to understand the functional effect of Kappa carrageenan on the quality of chicken meat  bites. To achieve this goal, Kappa carrageenan was added at 0, 0.5, 0.75 and 1.0 % levels for control, T1, T2 and T3 products, respectively.  Control bites contained 5 % added fat while treated samples were processed without added fat and the level of added fat of control sample was replaced with lean meat for the treatment groups. Results indicated addition of Kappa carrageenan improved the cooking yield,  emulsion stability and emulsion and cooked product pH up to 0.75 % added level. However, addition of Kappa carrageenan increased  shear force value, differences were non-significant. Colour coordinator, yellowness (b-value) and Chroma values increased significantly  while antioxidant parameters for ABTS activity was little affected. With regards to sensory quality, T1 and T2 samples showed nearly  similar but higher scores for all attributes than T3 sample. Thus, it was attributed that increasing of concentration of kappa carrageenan  above 0.75 % reduced sensory scores for all attributes. Finally, it was concluded that addition of kappa carrageenan in development of  chicken meat bites could help in reduction of fat level besides improving antioxidant activity, colour stability and consumer acceptability  of finished products. Thus, it was recommended to use upto 0.75% level of kappa carrageenan in development of chicken meat bites  for its fullest utilization of beneficial effects.
Keywords: Kappa carrageenan; Antioxidant activity; Sensory Attributes; Chicken Meat Bites